A powder metallurgy manufacturing method for a heavy truck steering booster oil pump stator
Through the powder metallurgy manufacturing method, combined with amorphous calcium phosphate powder and polyvinyl alcohol powder, a multi-step process is used to form a high-strength, high wear resistance and high impact strength power-added oil pump stator, which solves the problem of insufficient wear resistance and impact strength of the stator in the prior art, and achieves stable and efficient operation of the power-added pump.
Patent Information
- Application Number
- CN202411767688.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The stator of the current heavy-duty trucks has poor wear resistance and impact strength comprehensive performance, which may break brittle in high impact environments, and poor wear resistance leads to high noise and functional failure.
By adopting powder metallurgy manufacturing method, by preparing amorphous calcium phosphate powder and polyvinyl alcohol powder, combined with metal powders such as molybdenum, tungsten, nickel, graphite, etc., a booster oil pump stator with high hardness, high wear resistance and high impact strength is formed.
The internal hardness of the booster oil pump stator is achieved, and the external impact strength and wear resistance are high, which significantly improves the brittle breakage, deformation or wear of the stator during impact or friction. It is suitable for the use environment of the oil pump stator of heavy trucks and ensures the stable use of the booster pump.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil pumps for petroleum drilling, and more specifically, relates to a powder metallurgy manufacturing method for a stator of a heavy truck steering power oil pump. Background Art
[0002] The load capacity of heavy trucks is basically above 30 tons. During the steering process, the power pump needs to provide more power to ensure that the driver can turn the steering wheel more easily. Therefore, the stator in the power pump has very high requirements for hardness, wear resistance and impact resistance. In order to ensure the reliability of the stator, alloy cast iron is now selected for production. In the actual use of alloy cast iron, there are two restrictions: 1) The alloy content in alloy cast iron is very high. If its hardness is blindly improved, the impact resistance is easily limited, and it may be brittle in a high impact environment; 2) In the actual use of alloy cast iron stators, it is easy to wear and burr due to the poor wear resistance of the stator, resulting in loud noise when the power pump is working, and even causing the power pump to fail.
[0003] Therefore, it is particularly important to improve the wear resistance and impact strength of the power-assisted oil pump for heavy trucks while ensuring its own hardness. At present, it is urgent to prepare a power-assisted oil pump stator with high hardness, high wear resistance and high impact strength. Summary of the invention
[0004] 1. Problem to be solved
[0005] Aiming at the problem that the stator of a power steering oil pump for a heavy truck in the prior art has poor comprehensive performances such as wear resistance and impact strength, the present invention provides a powder metallurgy manufacturing method for a stator of a power steering oil pump for a heavy truck.
[0006] 2. Technical solution
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A powder metallurgy manufacturing method for a heavy truck steering booster oil pump stator of the present invention comprises the following steps:
[0009] (1) Preparing amorphous calcium phosphate powder;
[0010] (2) Primary pressing: prepare raw materials according to the mass ratio of amorphous calcium phosphate powder 0.8-3.5%, polyvinyl alcohol (PVA, which may be abbreviated as PVA in the following text) powder 1.2-4%, molybdenum powder 0.5-2%, tungsten powder 0.3-1.3%, nickel powder 1.6-5%, graphite powder 0.3-0.8%, zinc stearate 0.2-0.7%, molybdenum disulfide 0.5-1%, and the balance iron powder, and mix them evenly, wherein the sum of each component is 100%, and feed them into a mold, and preliminarily press them into a stator blank at a pressure of 10-100 MPa;
[0011] In the above steps, the mixture of the components is preliminarily pressed at a relatively small pressure, so that a stator blank having a certain degree of adhesion and porosity can be preliminarily obtained, so as to facilitate subsequent processes such as crystallization and pressing.
[0012] (3) Primary crystallization: placing the stator blank in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours to allow the amorphous calcium phosphate and polyvinyl alcohol in the stator blank to initially crystallize, wherein the pressure of the mixed gas is 101.325 kPa and the volume proportion of H2O is at least 10%;
[0013] In the above steps, H2O in the mixed gas can enter the pores of the stator blank at a specific temperature and pressure to promote the initial crystallization of amorphous calcium phosphate and polyvinyl alcohol, wherein the crystallinity of the PVA in the middle part is relatively high, because the amorphous calcium phosphate can promote the aggregation of PVA molecular chains to form crystal domains, while the relatively outer area of the stator blank is more easily exposed to the H2O gas, resulting in a certain swelling of the PVA, and the crystallinity is relatively low.
[0014] (4) Secondary pressing: The stator blank after initial crystallization is further pressed at a pressure of 600-800 MPa;
[0015] In the above steps, the secondary pressing can make part of the PVA with relatively poor crystallinity migrate to the inside of the stator blank, while the PVA and calcium phosphate with relatively high crystallinity in the middle part form a certain confined space. During the secondary pressing process, their position and confined space change relatively little, so that the stator blank forms a PVA component gradient and a crystallization gradient decreasing characteristic from the inside to the outside; at the same time, the higher pressure of the secondary pressing than the primary pressing makes the stator blank initially shaped, which is convenient for subsequent secondary crystallization and sintering.
[0016] (5) Secondary crystallization: The stator blank after secondary pressing is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume proportion of H2O is at least 10%;
[0017] In the above steps, crystallization continues under the strain after the secondary pressing, and the PVA crystallization gradient of the stator blank decreasing from the inside to the outside is further determined, while part of the amorphous calcium phosphate forms hydroxyapatite.
[0018] (6) Sintering: The stator blank after secondary crystallization is sent into a sintering furnace in a reducing atmosphere for sintering;
[0019] (7) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product.
[0020] In the above steps, high-temperature sintering and heat treatment not only make the metals metallurgically bonded, but also carbonize the PVA in the stator blank. Since the confined space formed by the calcium phosphate and PVA in the middle part limits the diffusion of carbonized carbon elements to a certain extent, after sintering, the carbonization of PVA with a crystallization gradient and a component gradient decreasing from the inside to the outside makes the carbon content of the stator product decrease from the inside to the outside. The middle area with higher carbon content combines with metal metallurgy to form a metal-carbon alloy phase with higher hardness. Moreover, this hardness will also show a gradient change from the inside to the outside due to the gradient change of carbon content, and will not cause the problem of cliff-like change in hardness, which lays the foundation for the overall tensile strength of the power steering oil pump stator product; and the outer area with lower carbon content makes the oil pump stator product have a certain toughness. In addition, the sintering process will cause the amorphous calcium phosphate to further generate hydroxyapatite, which improves the elastic modulus and wear resistance of the outer area of the power steering oil pump stator product, so that it has excellent impact buffering ability and wear resistance, thereby finally forming a power steering oil pump stator product with relatively high internal hardness and relatively high external impact strength and wear resistance.
[0021] Furthermore, the preparation method of the amorphous calcium phosphate powder in step (1) is as follows: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O are dissolved in 20 mL of ultrapure water, and mixed evenly to obtain solution A; 0.4 g of Na2HPO4·2H2O is dissolved in 20 mL of ultrapure water, and mixed evenly to obtain solution B; solution A is added to solution B, and the pH value is adjusted to 11 with 3 M NaOH solution, and the precipitate is collected by centrifugation at 8000 rpm for 5 minutes, and freeze-dried for 16 hours to obtain amorphous calcium phosphate powder. Wherein 3 M NaOH solution refers to 3 mol / L NaOH solution.
[0022] Furthermore, the adding solution A into solution B comprises: gradually dropping solution A into solution B at a dropping speed of 5 mL / min for reaction.
[0023] In the above steps, the dropping reaction is carried out at a dropping speed of 5 mL / min to avoid the generated calcium phosphate from aggregating into precipitation, thereby ensuring the subsequent stable generation of amorphous calcium phosphate.
[0024] Furthermore, in the step (2), the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed uniformly to obtain a mixed powder X, and then the mixed powder X is uniformly mixed with the remaining components and then pressed.
[0025] In the above steps, evenly mixing the amorphous calcium phosphate powder and the polyvinyl alcohol powder first allows them to be fully mechanically coupled, so that when they are mixed with other components, the amorphous calcium phosphate powder and the polyvinyl alcohol powder can be tightly combined, further ensuring the full formation of the intermediate confined space.
[0026] Furthermore, in the step (3), the volume ratio of H2O to N2 is 20%:80%.
[0027] Furthermore, in the step (4), the pressure of the secondary pressing is 650 MPa.
[0028] Furthermore, in the step (5), the volume ratio of H2O and N2 is 50%:50%.
[0029] Furthermore, in the step (6), the reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen in a volume ratio, the sintering temperature of the sintering furnace is 1100-1200° C., and the sintering treatment time is 2-5 hours.
[0030] Furthermore, in the step (7), the quenching temperature is 990-1120°C, the holding time is 1-3 hours, and the oil is cooled to room temperature; the tempering temperature is 600-720°C, and the tempering treatment time is 1-3 hours.
[0031] The present invention also protects a heavy truck power steering oil pump stator, which is prepared by any one of the preparation methods described above.
[0032] 3. Beneficial effects
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The powder metallurgy manufacturing method of the stator of a heavy-duty truck steering power oil pump of the present invention, wherein the middle region of the manufactured power oil pump stator with a higher carbon content is combined with metal metallurgy to form a metal-carbon alloy phase with higher hardness, thereby ensuring the overall tensile strength of the power oil pump stator product. The outer region with a lower carbon content makes the oil pump stator product have a certain toughness. At the same time, the generated hydroxyapatite improves the elastic modulus and wear resistance of the outer region of the power oil pump stator product, thereby finally forming a power oil pump stator product with relatively high internal hardness and relatively high external impact strength and wear resistance. The stator product greatly improves the problem of brittle fracture, deformation or wear of the stator during impact or friction, thereby adapting to the use environment of the oil pump stator of heavy trucks and ensuring the stable use of the power pump.
[0035] (2) A heavy truck power steering oil pump stator of the present invention is obtained by the preparation method of the present invention and has all the beneficial effects of the preparation method of the present invention. DETAILED DESCRIPTION
[0036] The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and not to limit the description of the features and characteristics of the present invention, so as to propose the best mode for performing the present invention, and to be sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs; the terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0038] The present invention is further described below in conjunction with specific embodiments. Example 1
[0039] This embodiment provides a powder metallurgy manufacturing method for a heavy truck power steering oil pump stator, which specifically includes the following steps:
[0040] (1) Preparation of amorphous calcium phosphate powder: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O were dissolved in 20 mL of ultrapure water and mixed to obtain solution A; 0.4 g of Na2HPO4·2H2O was dissolved in 20 mL of ultrapure water and mixed to obtain solution B; solution A was gradually added dropwise to solution B at a drop rate of 5 mL / min, the pH value was adjusted to 11 with 3 M NaOH solution, and the precipitate was collected by centrifugation at 8000 rpm for 5 minutes, and freeze-dried for 16 hours to obtain amorphous calcium phosphate powder;
[0041] (2) Primary pressing: preparing raw materials according to a mass ratio of 2.5% amorphous calcium phosphate powder, 3.5% polyvinyl alcohol powder, 1.4% molybdenum powder, 0.85% tungsten powder, 3.6% nickel powder, 0.6% graphite powder, 0.2% zinc stearate, 0.8% molybdenum disulfide, and the balance iron powder and mixing them evenly, wherein the sum of each component is 100%, feeding them into a mold, and preliminarily pressing them into a stator blank at a pressure of 30 MPa; wherein the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed evenly to obtain a mixed powder X, and then the mixed powder X is evenly mixed with the remaining components and then pressed;
[0042] (3) Primary crystallization: placing the stator blank in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours to allow the amorphous calcium phosphate and polyvinyl alcohol in the stator blank to initially crystallize, wherein the pressure of the mixed gas is 101.325 kPa, and the volume ratio of H2O to N2 is 20%:80%;
[0043] (4) Secondary pressing: the stator blank after initial crystallization is further pressed at a pressure of 650 MPa;
[0044] (5) Secondary crystallization: The stator blank after secondary pressing is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume ratio of H2O and N2 is 50%:50%;
[0045] (6) Sintering: The stator blank after secondary crystallization is sent to a sintering furnace in a reducing atmosphere for sintering. The reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen by volume. The sintering temperature of the sintering furnace is 1180°C and the sintering time is 3 hours.
[0046] (7) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product; wherein the quenching temperature is 1100°C, the holding time is 1.5 hours, and the oil is cooled to room temperature; the tempering temperature is 650°C, and the tempering time is 1 hour.
[0047] In order to further illustrate the unexpected technical effect achieved by the product of Example 1 of the present invention, the stator material of the power-assisted oil pump made in this embodiment is tested for relevant performances, and the test methods are as follows: 1) Tensile strength: Tested with reference to the standard GB / T2282002 "Metallic Material Room Temperature Tensile Test Method"; 2) Impact resistance: Tested with reference to the standard GB / T 229-2020 "Metallic Material Charpy Pendulum Impact Test Method", and the test methods of the subsequent embodiments are the same and will not be repeated. The test results are shown in Table 1.
[0048] Table 1. Performance comparison of power-assisted oil pump stators obtained in various implementation methods
[0049] Example 2
[0050] This embodiment provides a powder metallurgy manufacturing method for a heavy truck power steering oil pump stator, which specifically includes the following steps:
[0051] (1) Preparation of amorphous calcium phosphate powder: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O were dissolved in 20 mL of ultrapure water and mixed to obtain solution A; 0.4 g of Na2HPO4·2H2O was dissolved in 20 mL of ultrapure water and mixed to obtain solution B; solution A was gradually added dropwise to solution B at a drop rate of 5 mL / min, the pH value was adjusted to 11 with 3 M NaOH solution, and the precipitate was collected by centrifugation at 8000 rpm for 5 minutes, and freeze-dried for 16 hours to obtain amorphous calcium phosphate powder;
[0052] (2) Primary pressing: preparing raw materials according to a mass ratio of 2.5% amorphous calcium phosphate powder, 2.5% polyvinyl alcohol powder, 1.6% molybdenum powder, 1.2% tungsten powder, 2.4% nickel powder, 0.3% graphite powder, 0.4% zinc stearate, 0.5% molybdenum disulfide, and the balance iron powder, and mixing them uniformly, wherein the sum of each component is 100%, feeding them into a mold, and preliminarily pressing them into a stator blank at a pressure of 30 MPa; wherein the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed uniformly to obtain a mixed powder X, and then the mixed powder X is uniformly mixed with the remaining components and then pressed;
[0053] (3) Primary crystallization: placing the stator blank in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours to allow the amorphous calcium phosphate and polyvinyl alcohol in the stator blank to initially crystallize, wherein the pressure of the mixed gas is 101.325 kPa, and the volume ratio of H2O to N2 is 20%:80%;
[0054] (4) Secondary pressing: The stator blank after initial crystallization is further pressed at a pressure of 700 MPa;
[0055] (5) Secondary crystallization: The stator blank after secondary pressing is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume ratio of H2O and N2 is 50%:50%;
[0056] (6) Sintering: The stator blank after secondary crystallization is sent to a sintering furnace in a reducing atmosphere for sintering. The reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen by volume. The sintering temperature of the sintering furnace is 1100°C and the sintering time is 2 hours.
[0057] (7) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product; wherein the quenching temperature is 1050°C, the holding time is 2 hours, and the oil is cooled to room temperature; the tempering temperature is 700°C, and the tempering time is 1 hour.
[0058] In order to further illustrate the unexpected technical effect achieved by the product of Example 2 of the present invention, relevant performance tests were conducted on the stator material of the power steering oil pump made in this embodiment. The test results are shown in Table 1. Example 3
[0059] This embodiment provides a powder metallurgy manufacturing method for a heavy truck power steering oil pump stator, which specifically comprises the following steps:
[0060] (1) Preparation of amorphous calcium phosphate powder: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O were dissolved in 20 mL of ultrapure water and mixed to obtain solution A; 0.4 g of Na2HPO4·2H2O was dissolved in 20 mL of ultrapure water and mixed to obtain solution B; solution A was gradually added dropwise to solution B at a drop rate of 5 mL / min, the pH value was adjusted to 11 with 3 M NaOH solution, and the precipitate was collected by centrifugation at 8000 rpm for 5 minutes, and freeze-dried for 16 hours to obtain amorphous calcium phosphate powder;
[0061] (2) Primary pressing: preparing raw materials according to a mass ratio of 2.5% amorphous calcium phosphate powder, 4% polyvinyl alcohol powder, 1.7% molybdenum powder, 0.6% tungsten powder, 1.9% nickel powder, 0.5% graphite powder, 0.5% zinc stearate, 1% molybdenum disulfide, and the balance iron powder and mixing them evenly, wherein the sum of the components is 100%, feeding them into a mold, and preliminarily pressing them into a stator blank at a pressure of 40 MPa; wherein the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed evenly to obtain a mixed powder X, and then the mixed powder X is evenly mixed with the remaining components and then pressed;
[0062] (3) Primary crystallization: placing the stator blank in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours to allow the amorphous calcium phosphate and polyvinyl alcohol in the stator blank to initially crystallize, wherein the pressure of the mixed gas is 101.325 kPa, and the volume ratio of H2O to N2 is 20%:80%;
[0063] (4) Secondary pressing: the stator blank after initial crystallization is further pressed at a pressure of 600 MPa;
[0064] (5) Secondary crystallization: The stator blank after secondary pressing is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume ratio of H2O and N2 is 50%:50%;
[0065] (6) Sintering: The stator blank after secondary crystallization is sent to a sintering furnace in a reducing atmosphere for sintering. The reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen by volume. The sintering temperature of the sintering furnace is 1200°C and the sintering time is 2 hours.
[0066] (7) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product; wherein the quenching temperature is 1120°C, the holding time is 1 hour, and the oil is cooled to room temperature; the tempering temperature is 600°C, and the tempering time is 1 hour.
[0067] In order to further illustrate the unexpected technical effect achieved by the product of Example 3 of the present invention, relevant performance tests were conducted on the stator material of the power steering oil pump made in this embodiment. The test results are shown in Table 1.
[0068] Comparative Example 1
[0069] This comparative example provides a powder metallurgy manufacturing method for a heavy truck steering power oil pump stator, which specifically includes the following steps:
[0070] (1) Preparation of amorphous calcium phosphate powder: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O were dissolved in 20 mL of ultrapure water and mixed to obtain solution A; 0.4 g of Na2HPO4·2H2O was dissolved in 20 mL of ultrapure water and mixed to obtain solution B; solution A was gradually added dropwise to solution B at a drop rate of 5 mL / min, the pH value was adjusted to 11 with 3 M NaOH solution, and the precipitate was collected by centrifugation at 8000 rpm for 5 minutes, and freeze-dried for 16 hours to obtain amorphous calcium phosphate powder;
[0071] (2) Pressing: preparing raw materials according to the mass ratio of 2.5% amorphous calcium phosphate powder, 3.5% polyvinyl alcohol powder, 1.4% molybdenum powder, 0.85% tungsten powder, 3.6% nickel powder, 0.6% graphite powder, 0.2% zinc stearate, 0.8% molybdenum disulfide, and the balance iron powder, and mixing them evenly, wherein the sum of each component is 100%, feeding them into a mold, and pressing them at a pressure of 650 MPa to form a stator blank; wherein the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed evenly to obtain a mixed powder X, and then the mixed powder X is evenly mixed with the remaining components and then pressed;
[0072] (3) Crystallization: The pressed stator blank is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume ratio of H2O and N2 is 50%:50%;
[0073] (4) Sintering: The crystallized stator blank is sent to a sintering furnace in a reducing atmosphere for sintering. The reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen by volume. The sintering temperature of the sintering furnace is 1180°C and the sintering time is 3 hours.
[0074] (5) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product; wherein the quenching temperature is 1100°C, the holding time is 1.5 hours, and the oil is cooled to room temperature; the tempering temperature is 650°C, and the tempering time is 1 hour.
[0075] The main difference between Comparative Example 1 and Example 1 is that the steps of primary pressing and primary crystallization are eliminated, and after the components are evenly mixed, they are directly pressed at a pressure of 650 MPa to form a stator blank for subsequent steps such as crystallization and sintering.
[0076] The stator material of the power-assisted oil pump manufactured according to this embodiment is subjected to relevant performance tests, and the test results are shown in Table 1.
[0077] Comparative Example 2
[0078] This comparative example provides a powder metallurgy manufacturing method for a heavy truck power steering oil pump stator. The specific steps are basically the same as those of comparative example 1, with the main difference being that after pressing, sintering is performed directly without using the crystallization in step (3).
[0079] The stator material of the power steering oil pump manufactured according to this embodiment is subjected to relevant performance tests, and the test results are shown in Table 1.
[0080] By comparing Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the booster oil pump stator prepared in the embodiment of the present application can not only improve the tensile strength to a certain extent and ensure that it is above 1380MPa, but also can greatly improve the impact resistance and wear resistance, thereby ensuring the various performances of the stator at the same time, so as to meet the needs of the heavy truck oil pump stator in complex use environments such as impact and friction. Among them, the stator blank of Comparative Example 1 has a certain crystallization gradient after crystallization, but the impact resistance of the final stator material is not effectively improved. This is probably because there is no one-time pressing and crystallization effect to form an obvious component gradient and crystallization gradient in the stator blank, resulting in the stator formed by sintering being relatively easy to break as a whole. In Comparative Example 2, even if the amorphous calcium phosphate powder and polyvinyl alcohol powder components in the process of the present invention are added, it is difficult to form a specific component gradient and crystallization gradient without the action of a specific pressing and crystallization process, resulting in a relatively uniform alloy phase of the final stator product. On the contrary, the introduction of PVA causes the carbonization degree in the alloy phase of the stator surface layer to be higher than when PVA is not added, and it is easier to break.
[0081] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and any such modifications and variations, if any, will fall within the scope of the present invention described herein. In addition, the background art is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.
[0082] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.
[0083] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail. When flow, power, refractive index, time, or other values or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.
Claims
1. A powder metallurgy manufacturing method for a heavy truck power steering oil pump stator, characterized in that: The steps include: (1) Preparing amorphous calcium phosphate powder; (2) Primary pressing: prepare raw materials according to the mass ratio of amorphous calcium phosphate powder 0.8-3.5%, polyvinyl alcohol powder 1.2-4%, molybdenum powder 0.5-2%, tungsten powder 0.3-1.3%, nickel powder 1.6-5%, graphite powder 0.3-0.8%, zinc stearate 0.2-0.7%, molybdenum disulfide 0.5-1%, and the balance iron powder, and mix them evenly, wherein the sum of each component is 100%, and feed them into a mold, and preliminarily press them into a stator blank at a pressure of 10-100 MPa; (3) Primary crystallization: placing the stator blank in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours to allow the amorphous calcium phosphate and polyvinyl alcohol in the stator blank to initially crystallize, wherein the pressure of the mixed gas is 101.325 kPa and the volume proportion of H2O is at least 10%; (4) Secondary pressing: The stator blank after initial crystallization is further pressed at a pressure of 600-800 MPa; (5) Secondary crystallization: The stator blank after secondary pressing is placed in a mixed gas environment of H2O and N2 at a temperature of 95°C for 24 hours for further crystallization, wherein the pressure of the mixed gas is 101.325 kPa and the volume proportion of H2O is at least 10%; (6) Sintering: The stator blank after secondary crystallization is sent into a sintering furnace in a reducing atmosphere for sintering; (7) Heat treatment: The sintered product is quenched and tempered to obtain a heavy truck power steering pump stator product.
2. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: The preparation method of the amorphous calcium phosphate powder in step (1) is as follows: 0.8 g of CaCl2·2H2O and 0.3 g of MgCl2·6H2O are dissolved in 20 mL of ultrapure water, and the mixture is mixed uniformly to obtain solution A; 0.4 g of Na2HPO4·2H2O is dissolved in 20 mL of ultrapure water, and the mixture is mixed uniformly to obtain solution B; solution A is added to solution B, the pH value is adjusted to 11 with 3 M NaOH solution, the precipitate is collected by centrifugation at 8000 rpm for 5 minutes, and the precipitate is freeze-dried for 16 hours to obtain amorphous calcium phosphate powder.
3. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 2, characterized in that: The adding solution A into solution B comprises: gradually dropping solution A into solution B at a dropping speed of 5 mL / min for reaction.
4. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (2), the amorphous calcium phosphate powder and the polyvinyl alcohol powder are firstly mixed uniformly to obtain a mixed powder X, and then the mixed powder X is uniformly mixed with the other components and then pressed.
5. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (3), the volume ratio of H2O to N2 is 20%:80%.
6. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (4), the pressure of the secondary pressing is 650 MPa.
7. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (5), the volume ratio of H2O and N2 is 50%:50%.
8. The powder metallurgy manufacturing method for a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (6), the reducing atmosphere is a mixed gas of 20% hydrogen and 80% nitrogen in a volume ratio, the sintering temperature of the sintering furnace is 1100-1200° C., and the sintering treatment time is 2-5 hours.
9. The powder metallurgy manufacturing method of a heavy truck power steering oil pump stator according to claim 1, characterized in that: In the step (7), the quenching temperature is 990-1120°C, the holding time is 1-3 hours, and the steel is oil-cooled to room temperature; the tempering temperature is 600-720°C, and the tempering treatment time is 1-3 hours.
10. A heavy truck power steering oil pump stator, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
Titanium alloy powder, and preparation method and application thereof
CN104942283A
Ultrahigh-purity spherical tungsten powder and preparation method thereof
CN114393214A